Dual Role for Autophagy in Lipid Metabolism in Arabidopsis. Issue 7 (29th April 2019) - Fan, Jilian; Yu, Linhui; Xu, Changcheng
Abstract : Autophagy regulates both lipid droplet biogenesis and turnover in plants. Abstract: Autophagy is a major catabolic pathway whereby cytoplasmic constituents including lipid droplets (LDs), storage compartments for neutral lipids, are delivered to the lysosome or vacuole for degradation. The autophagic degradation of cytosolic LDs, a process termed lipophagy, has been extensively studied in yeast and mammals, but little is known about the role for autophagy in lipid metabolism in plants. Organisms maintain a basal level of autophagy under favorable conditions and upregulate the autophagic activity under stress including starvation. Here, we demonstrate that Arabidopsis ( Arabidopsis thaliana ) basal autophagy contributes to triacylglycerol (TAG) synthesis, whereas inducible autophagy contributes to LD degradation. We found that disruption of basal autophagy impedes organellar membrane lipid turnover and hence fatty acid mobilization from membrane lipids to TAG. We show that lipophagy is induced under starvation as indicated by colocalization of LDs with the autophagic marker and the presence of LDs in vacuoles. We additionally show that lipophagy occurs in a process morphologically resembling microlipophagy and requires the core components of the macroautophagic machinery. Together, this study provides mechanistic insight into lipophagy and reveals a dual role for autophagy in regulating lipid synthesis and turnover in plants.